Post-soviet Conceptions of the System of Financial Law: Philosophic-methodological Analysis - Patsurkivskyy, Petro (Masaryk University, 2015)
The article deals with the analysis of a scientific research status of the problem in the science of financial law from the perspective of system approach. It is shown that the post-soviet science of financial law still understands this law as, a determined by the environment, mechanical aggregate of legal norms created or authorized by the state. It is proved that in post-soviet financial law there remained all three basic conceptions of financial law formulated by soviet legal scholars: fund conception, institutional conception, subject conception. It is substantiated that the system philosophic-methodological approach should be applied for true scientific cognition of the system of financial law as a procedural reality.
Keywords: System of financial law; fund conception of the system of financial law; institutional conception of the system of financial law; subject concep- tion of the system of financial law; system philosophic-methodological approach